Wynagrodzenie robotników w kapitalizmie w encyklikach społecznych Jana Pawła II — analiza proponowanych rozwiązań w świetle teorii szkoły austriackiej - Kubisz, Ryszard J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
There are many authors writing on Catholic social teaching. Some support free market interpretation of writings of St. John Paul II, some tend to stress its pro-social elements. The purpose of our paper is to analyse three social encyclicals of Polish Pope and compare his opinion about labour and wages under capitalist regime with the most consequent proponents of free market capitalism — the Austrian school economists. Careful reading of St. John Paul II’s writings shows his very critical attitude to capitalism, especially in its beginnings. Yet his criticism is not equipped with elaborated economic theory and is just a group of ideas, based mostly on ethical reflections. The most famous of those is the notion of the family wage. The notion, that if imposed by legislation, would bring many effects unwanted and unrealised by the Pope. The economic analysis of the family wage concept shows that it can be more harmful than beneficial to the society. Furthermore, Pope’s acceptance for social security places his views surprisingly close to current welfare state. General view of three social encyclicals of St. John Paul II prove his less pro-capitalistic attitude than many scholars think
Keywords: rodzina; płace; Jan Paweł II (papież; 1920-2005); praca